2011
DOI: 10.1016/j.jneumeth.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Demon Voltammetry and Analysis software: Analysis of cocaine-induced alterations in dopamine signaling using multiple kinetic measures

Abstract: The fast sampling rates of fast scan cyclic voltammetry make it a favorable method for measuring changes in brain monoamine release and uptake kinetics in slice, anesthetized, and freely moving preparations. The most common analysis technique for evaluating changes in dopamine signaling uses well-established Michaelis-Menten kinetic methods that can accurately model dopamine release and uptake parameters across multiple experimental conditions. Nevertheless, over the years, many researchers have turned to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
359
2
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(376 citation statements)
references
References 29 publications
6
359
2
9
Order By: Relevance
“…Few voltammetric studies have already reported similar changes in DA overflow across psychostimulant concentrations, being the inhibitory effect on DA overflow interpreted as secondary to presynaptic D2 autoreceptor activation (21)(22). However, this is not possible because the depression of DA overflow occurs in the presence of the D2 antagonist sulpiride and also in the DAT-CI striatal slices (where an activation of D2 autoreceptors by an enhanced extracellular DA level does not occur).…”
Section: Discussionmentioning
confidence: 99%
“…Few voltammetric studies have already reported similar changes in DA overflow across psychostimulant concentrations, being the inhibitory effect on DA overflow interpreted as secondary to presynaptic D2 autoreceptor activation (21)(22). However, this is not possible because the depression of DA overflow occurs in the presence of the D2 antagonist sulpiride and also in the DAT-CI striatal slices (where an activation of D2 autoreceptors by an enhanced extracellular DA level does not occur).…”
Section: Discussionmentioning
confidence: 99%
“…Once the extracellular DA response was stable for three consecutive stimulations, a cumulative concentration response curve of the KOR agonist, U50,488 (10, 30, 100, 300, 1000 nM), was run by bath applying the drug to NAc slices. All FSCV data were analyzed using the Demon Voltammetry and Analysis software (Yorgason et al, 2011). DA-stimulated release parameters were determined from stabilized signals using a Michaelis-Menten kinetics-based algorithm (Ferris et al, 2013).…”
Section: Ex Vivo Fast Scan Cyclic Voltammetry (Fscv)mentioning
confidence: 99%
“…This was used to convert an electrical current to a DA concentration. Demon Voltammetry and Analysis software (Yorgason et al, 2011) was used to analyze FSCV data. Eighteen hours after the last session of AMPH selfadministration, tissues from the midbrain (including VTA and SN) or the whole striatum (ventral and dorsal striatum) of AMPH self-administering rats and controls were dissected using a rat brain matrix.…”
Section: Fast-scan Cyclic Voltammetry For Measuring the Function Of Dmentioning
confidence: 99%